From transcendental egology to orientation theory: Toward a mereological foundation for the different senses of the “self” in conscious experience - Guardiola, Joan González (Frontiers in Psychology, 2022)
In the present work, we aim to make a contribution to the origins of the notion of “minimum self” in Husserl's phenomenology. Starting from the difference between the philosophy of the subject and the philosophy of the self, the aim of this research is to show that the Cartesian association between both philosophies would not exactly correspond to the conception of the self, as we find it in Edmund Husserl's works. With this, we intend to nuance Heidegger's accusation of Husserl's “Cartesianism,” At the same time, we show how a detailed analysis of the “senses of the self” in Husserl's phenomenology allows extracting the notion of “minimal self” as it has been introduced in the current and lively debate between psychiatry and phenomenology. In our research, we also show that in order to move the theory of the transcendental ego toward the theory of the orientation of the life of consciousness, it is necessary to consider the foundation of the concepts of ego in the technical vocabulary of the formal mereology of the Husserl's third “Logical Investigation.”